Peranan Visum Et Repertum dalam Mengungkap Tindak Pidana Pembunuhan Perspektif Hukum Islam di Pengadilan Negeri Sungguminasa - Nur Ahmad U; Kasjim Salenda (Universitas Islam Negeri Alauddin Makassar, 2021)
The main problem of this research is related to the role of Visum Et Repertum in uncovering the crime of murder. Islamic Law Perspective Case Study Number 438/Pid. b/ 2020/ PN. Sungguminasa. To answer these problems, the authors use a methodology, namely: 1) Interviews with judges who handle cases described in the background. 2) Data analysis, namely the author uses qualitative data analysis, in which the author uses qualitative descriptive. The results of the study are that although it is not absolute that there is a visum et revertum in proving criminal cases, but to strengthen the judge's confidence, so that visum et revertum should always exist, especially criminal acts whose object is the human body, and visum et repertum is a piece of evidence which is not binding on judges, so that the visum et repertum is only a complementary evidence. However, in certain cases where the available evidence is minimal or lacking, visum et repertum is the main evidence that must be used as a basis by the judge. So that the visum et repertum can also be used as evidence that is binding and has legal force so that the visum et repertum issued by a team of expert doctors is a necessity, especially regarding cases of murder crimes. The position of visum et repertum in Islamic law is as the application of ijtihad for judges to obtain truth and justice, namely as evidence, precisely as written evidence or in Islam known as al-bayyinah because it can create benefit for mankind.Keywords: Visum Et Repertum; Cases of Murder; Islamic Law